Graphic humor to promote mathematics learning - Menezes, Luís (2020)
This paper presents an exploratory study, under development in Portugal, in which one intends to understand the role that mathematical tasks based on graphic humor (comic strips) can play in the learning of Mathematics, in particular, in the written communication, of students at the end of primary education (4th and 6th grades). For this purpose, two classes were chosen, in which mathematical tasks, based on graphic humor, were proposed, and students were encouraged to write about them. The study followed a qualitative methodology and data collection took place from: (i) task resolutions; and (ii) field notes. To analyse the impact of mathematical tasks based on graphic humor in the written communication of students, we consider: (i) Appreciation of the task's graphic humor; (ii) understanding and solving the task; and (iii) construction, organization and consistency of the text. The results of the study reveal that mathematical tasks based on graphic humor are welcomed by young students, who appreciate humor. Students respond to the request to produce written texts, which describe the comic strips, and solve with enthusiasm the mathematical problems present in the situations. Mathematical writing, well-structured and using mathematical language consistently, is decisive to promote reasoning, develop communication skills and for learning mathematics.